A study on activated carbon and carbon nanotube based consolidated composite adsorbents for cooling applications. (1st September 2022) - Jahan, Israt; Rocky, Kaiser Ahmed; Pal, Animesh; Rahman, Md Matiar; Saha, Bidyut Baran
Graphical abstract: MWCNT based composites enhance the thermal conductivity of the parent activated carbon, and they exhibit a higher volumetric cooling effect than other promising composites. Highlights: Synthesis of Activated carbon (AC)-multiwalled carbon nanotube (MWCNT) composites. AC-MWCNT composites possess higher packing density than parent AC. AC-MWCNT composites reveal improved thermal conductivity over parent AC. MWCNT contributes to the CO2 adsorption capacity of composite adsorbents. AC-MWCNT composites exhibit improved SCE and COP over other AC-based composites. Abstract: Activated carbon (AC)/CO2 pair is very promising for developing an efficient adsorption cooling system (ACS). However, the low packing density and poor heat transfer properties of activated carbon-based ACS prevent their widespread adoption. Addressing these issues, this study focuses on the synthesis and characterization of AC-based consolidated composites comprising Maxsorb III (one type of AC) as adsorbent, multi-walled carbon nanotube (MWCNT) as thermal conductivity enhancer (TCE), and polyvinyl alcohol (PVA) as the binder. The influence of MWCNT on the porous properties, thermal diffusivity, thermal conductivity, and CO2 adsorption capacity of composite adsorbents has been experimentally investigated. Besides, performance parameters, including the specific cooling effect (SCE) and coefficient of performance (COP), have been theoretically determined under different working conditions. Porous properties results show that developed composites are microporous like AC and exhibit high surface area and pore volume compared to other AC-based composite adsorbents developed so far. The incorporation of MWCNT into AC results in enhancing packing density, thermal diffusivity, and conductivity. One of the developed composites exhibits 2.47 and 3.5 times higher packing density and thermal conductivity than that of parent AC. Besides, the CO2 adsorption study concludes regarding the contribution of MWCNT in the CO2 adsorption capacity of composite adsorbents, which in turn results in the improved CO2 uptake, SCE, and COP over other AC composites found in the literature. This study's findings will greatly stimulate the development of an efficient and compact adsorption cooling system.